Bone mineral density in patients with chronic spinal cord injury: An observational study - Ratnakar, Lal; Laisram, Nonica; Banoth, Kiran; Badhal, Suman; Dhiman, Nitish (Asian Journal of Medical Sciences, 2023)
Background: Spinal cord injury (SCI) is accompanied by loss of bone mass caused by accelerated bone remodeling, with bone resorption exceeding bone formation which causes net bone loss. The significance of osteoporosis after SCI is that it results in skeletal fragility and an increased risk of fractures. Complications from fractures lead to an increase not only in the associated morbidity and mortality, but also in the health-care costs that they generate. Aims and Objectives: The objective of the study was to evaluate bone mineral density (BMD) in patients with SCI in Indian population and to determine the effects of the neurological level, severity of injury, and mobility status on BMD. Materials and Methods: This study was a prospective and observational study conducted on 52 chronic SCI patients. After detailed history and examination, patients were assessed using American spinal injury association impairment scale following which BMD was assessed by Dual Energy X-ray Absorptiometry Scan. Correlation between the T score and neurological level, severity of injury and mobility status was assessed. P<0.05 was considered statistically significant. Results: Out of 52 patients included, 41 were having complete SCI and 35 were non-ambulatory. T score was significantly (P<0.001) lower in lumbar spine and both femur in complete SCI patients. The T score was indicative of increased osteoporosis in non-ambulatory patients. BMD did not differ significantly (P<0.059) in patients with relation to various neurological levels. Conclusion: From this study, we conclude that osteoporosis is commonly present in patients with complete SCI and non-ambulatory was more affected. Early mobilization of these patients reduces the development of osteoporosis.